Asia's new regionalism and global role : agenda for the East Asia Summit - Kumar, Nagesh, 1958-; Kesavapany, K.; Chaocheng, Yao.; Research and Information System for the Non-aligned and Other Developing Countries; Institute of Southeast Asian Studies (New Delhi : Research and Information System for Developing Countries, 2008)
Contributed articles presented at a series of conferences held at various places between 2004-2005.
Includes bibliographical references.
Keywords: Asia -- Economic integration -- Congresses